2022
DOI: 10.1021/acs.jnatprod.1c00879
|View full text |Cite
|
Sign up to set email alerts
|

Jatrophane Diterpenoids with Kv1.3 Ion Channel Inhibitory Effects from Euphorbia helioscopia

Abstract: Chemical investigation of bioactive components from the whole plant of Euphorbia helioscopia resulted in the isolation and identification of 17 new jatrophane diterpenoids, namely, heliojatrone D (1) and helioscopids A−P (2−17), along with 11 known analogues (18−28). The structural elucidation of the new diterpenoids was achieved by the comprehensive analysis of HRESIMS, NMR, and X-ray crystallographic data, as well as using electronic circular dichroism. Structurally, heliojatone D (1) is the fourth natural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Notably, the Kv1.3 inhibitory effect of lathyrane diterpenoids was discovered for the first time. According to our previous investigations on jatrophane diterpenoids, 11,12 esterification of jatrophanes may significantly alter their Kv1.3 inhibition activity. Further modifications of the lathyrane diterpenoids are needed for developing potential lead compounds for the treatment of autoimmune diseases.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Notably, the Kv1.3 inhibitory effect of lathyrane diterpenoids was discovered for the first time. According to our previous investigations on jatrophane diterpenoids, 11,12 esterification of jatrophanes may significantly alter their Kv1.3 inhibition activity. Further modifications of the lathyrane diterpenoids are needed for developing potential lead compounds for the treatment of autoimmune diseases.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Diterpenoids are of common occurrence in plants of genus Euphorbia (Euphorbiaceae), with varied structural diversity and biological activities . Recently, diterpenoids with jatrophane, myrsinane, premyrsinane, and cyclomyrsinane skeletons isolated from E. guyoniana , E. falcata , and E. dulcis were found to be selective blockers of G protein-activated inwardly rectifying potassium ion channel (GIRK). , We have also continuously reported that some ingenane-related and jatrophane-related diterpenoids from E. peplus and E. helioscopia display inhibitory effect against Kv1.3 ion channel. Nonetheless, no data are available for comparing the Kv1.3 inhibitory effects among these diverse diterpenoid skeletons.…”
mentioning
confidence: 99%
“…Notably, a NOE correlation between H-2' (6') (δ H 8.0) of the OBz-3 and methyl of OAc-15 (δ H 2.16) indicated the β-configuration of OAc-15. [9] Moreover, based on NOE cross-peaks between H-5 and H-13, H-13 was assigned a β-orientation. The vicinal protonÀ proton coupling constant of H-13/H-14 ( 3 J 13/14 = 5.8) further indicated an orthogonal relationship between the two vicinal protons, establishing an α-orientation for H-14.…”
Section: Resultsmentioning
confidence: 99%
“…Euphorbia diterpenoids, the principal and distinguishing chemical constituents of this plant, have garnered growing interest from both chemical and biological communities. This fascination is attributed to their diverse biological activities, including potential anti‐inflammatory, antitumor, and multidrug‐resistance‐modulating effects, [6–10] Furthermore, these diterpenoids boast a broad spectrum, structural diversity, owing to their various macrocyclic and polycyclic frameworks with multiple oxygen‐containing functionalities [11–13] …”
Section: Introductionmentioning
confidence: 99%
“…However, according to the aforementioned X-ray crystallographic results and biogenetic pathways, H-5 remains α-oriented. These observations indicate that only employing 1 H NMR coupling constants in stereochemical assignments of the germacranolides does not permit unequivocal results because of the conformational flexibility of the ten-membered ring. , It is also challenging to determine unambiguous stereochemical assignments for macrocyclic terpenoids. …”
Section: Results and Discussionmentioning
confidence: 99%